Orbital cellulitis after infiltration anaesthesia for sling surgery in a case of congenital ptosis: a case report - Dwivedi, Kshama; Singh, Vibha; Sachan, Shubhi; Katiyar, Divya (International Journal of Research in Medical Sciences, 2024)
Orbital cellulitis has been reported as a complication of various ophthalmic surgeries. But to the best of our knowledge this is first case of orbital cellulitis following sling surgery. It was an observational study. An eight-year-old male, developed orbital cellulitis after ptosis surgery. He presented to us after one week with fever, periorbital swelling, chemosis and restricted ocular movement. He was successfully managed without any sequelae. Early suspicion and prompt management are the key to successful management of orbital cellulitis following ophthalmic surgeries.